Pengaruh Kandungan Komponen Minor dari Minyak Kelapa Sawit (Elaeis guineensis Jacq.) Terhadap Aktivitas Antioksidan pada Proses Pemurnian Karotenoid - Sinaga, Ahmad Gazali Sofwan; Siahaan, Donald (UI Scholars Hub, 2015)
Palm oil contains carotenoid and vitamin E which possess antioxidant properties. A long exposure of heat and chemical substances during the purification process may lower antioxidant activity. This research was conducted to compare antioxidant activity of carotenoid and vitamin E obtained from each stage of three continuous purification process (transesterification, solvolytic micellization, and saponification). Total carotenoid concentration was analyzed by UV-visible spectrophotometer at λ 446 nm and total vitamin E concentration was analyzed by high-performance liquid chromatography, while ester and triglyceride concentration were analyzed by gas chromatography. Antioxidant activity was measured by DPPH assay with incubation time in 60 minutes. The highest concentration of carotenoid (229,968 mcg/ml) was extracted from saponification process, yet the highest concentration of vitamin E (97.64 mcg/ml) was extracted from transesterification process. The highest antioxidant activity of carotenoids and vitamin E was obtained from the transesterification process, while other processes had lower antioxidant activity, so it can be concluded that exposure to heat and excessive chemical substances couldimpact on antioxidant activity.